EFL Students’ Intercultural Awareness in Multicultural Classroom: A Narrative Inquiry - Saharani, Annisa Aulia (Institut Agama Islam Negeri (IAIN) Kediri, 2023)
Being an intercultural speaker has become a necessity in global communication. Multicultural classes have a positive impact on intercultural learning because students from various cultural backgrounds come together to learn English. Therefore, this study aims to explore and narrate the development of intercultural awareness achieved by the students based on their experiences in a multicultural class setting. This study is a qualitative research with a narrative inquiry method. The participants in this study are three Indonesian students and two Thai students who are majoring in English Education and are in the same class at one of the universities in Indonesia. Data was collected through in-depth questionnaires with open-ended questions. The results of the study show that the students in the multicultural class have a good level of intercultural awareness. They have mastered all levels of intercultural awareness, from basic cultural awareness, advanced cultural awareness to intercultural awareness. Although they faced obstacles such as language barriers and limited exposure to the target language's culture in the class, they are able to practice tolerance and respect for different cultures. In addition, they have been able to adapt and integrate their cultural knowledge to be implemented in communication with speakers from different cultures